Fiber quality and fertility in male alpacas in the Cusco region of Peru - Pacheco, Joel; Bengtsson, Fanny; Killander, Jakob; Franco, Francisco; Lundeheim, Nils; Varga, Csaba; Båge, Renée; Morrell, Jane M. (Frontiers in Veterinary Science, 2024)
Introduction High testosterone levels might be associated with coarser fiber in alpacas, affecting fiber quality. In the husbandry systems employed in the Andes, males with higher libido might have an increased frequency of successful matings than males with lower libido. This study aimed to determine some of the factors affecting fiber quality in Peruvian alpacas and to evaluate the association between fiber quality and male mating behavior. Methods The study population consisted of 189 adult male alpacas at La Raya, Cusco, Peru, at 4,400 m above sea level, belonging to the National University of San Marcos, Lima, and the National University of San Antonio Abad of Cusco. Fiber samples were collected from male alpacas in September 2015; body condition score (BCS) was evaluated. After washing and drying, the fiber samples were analyzed using an Optical Fiber Diameter Analyser 2000; linear regression analysis between predictor variables (location of alpacas, age, BCS, and fiber color) and fiber quality outcomes was conducted. Fertility data were available only for some males belonging to San Marcos University, consisting of hand-written records from the breeding season January to April 2015; individual fertility quotients were calculated for each male. Results Age was associated with fiber quality, young alpacas having the finest fibers (p < 0.05). An increased BCS was associated with increased fiber length, fiber diameter and spinning fineness, but decreased comfort factor (p < 0.05). White fibers were thinner (p = 0.05) than colored fibers, with lower comfort factor and spinning fineness. A significant association between the fertility quotient and fiber curvature was observed (p = 0.018). Discussion These results suggest that careful selection of breeding individuals and attention to husbandry could result in improved fiber quality among alpaca herds in Peru. However, it would be advisable to increase the number of males studied, using more reliable methods for evaluating male fertility and pregnancy diagnosis than were available for this study.